ANALYSIS OF UKRAINIAN PHARMACEUTICAL MARKET RETAIL SEGMENT DEVELOPMENT - Natalia Bogdan (Journal of Global Pharma Technology, 2018)
The pharmaceutical market is an important part of the system of pharmaceutical provision of the country. In modern conditions, the pharmaceutical market performs many functions, among which the social function is one of the most important. The aim of our study was to analyze the dynamics of the development of the Ukrainian pharmaceutical market in the conditions of the socio-economic and financial crisis in the country. We conducted dynamics analysis of pharmacy sales development in retail sector of pharmaceutical market (2011-2017). We used historical, comparative, logical, graphical, and mathematical-statistical methods of scientific search. As a result of studies we have found that during 2011-2017 the retail segment of Ukrainian pharmaceutical market had zigzag-shaped development dynamics. We distinguished three main stages of its development. So, during the first stage (2011-2013), we observed positive growth dynamics of pharmacy sales expressed in hryvnia, U.S. dollar, and package pieces. What is more, increase of pharmacy sales' indicators, expressed in hryvnia and U.S. dollar, did not differ significantly. The second, the most difficult, period lasted for two years (2014-2015). This period was characterized with decrease of sales' volume, expressed in U.S. dollar and in natural indexes (package pieces). In 2015 the lowest indexes of pharmacy sales, expressed in U.S. dollar (22.75 million U.S. dollars), and in natural indexes (1507.1 million of package pieces), were observed. Increase (38.0%) of sales' volumes, expressed in hryvnia, which was observed in 2015, was due to devaluation of national currency. The third stage of market development started in 2016 and is continuing still. In the retail segment an increase in volume of pharmacy sales, expressed in hryvnia – by 22.0%, in U.S. dollar – by 4.0%, and in package pieces – by 6.0%, has been observed from2016. Inthe conditions of relative stabilization of U.S. dollar rate in 2017, growth of sales' volume in U.S. dollar was 17.0%, and in natural indexes – only 5.0%. Gradual slowdown of one sale weighted average cost growth, beginning in 2016, is an important positive characteristic of pharmacy sales market development. For example, in 2015 this index grew by 41.0%, in 2016 – by 16.0%, and in 2017 – only by 10.0%. Of special note is the fact of gradual increase of sales' volume per capita, expressed in U.S. dollar. For example, in 2015 this index was 36.04, in 2016 – 37.24, and in 2017 – 44.09 U.S. dollars.Retail segment of Ukrainian pharmaceutical market, in the conditions of political and social-economical crisis in the country, has shown the complex nature of its development. Devaluation of national currency in the conditions of high dependence of Ukrainian pharmaceutical market on import significantly influenced the dynamics of pharmacy sales. In these conditions Ukrainian consumers of pharmaceutical services should not be left alone with the problem of significant increase of prices of medical products. Implementation of systemic reforms in health protection, and development of consistent state policy of Ukrainian pharmaceutical market development and medicines' consumption regulation provide the real way out of this situation.